Guía práctica para manejo de pastos en campos de golf - Witteveen, Gordon (John Wiley & Sons, 2003)
Painstakingly translated from the best-selling English version, this popular guide offers the same expert knowledge of green-keeping for non-English speaking professionals and workers. It provides hundreds of helpful tips that are used by professionals daily. Practical information, presented in a step-by-step format, includes green maintenance and management, maintaining consistent bunkers, topdressing and aerification, using chemicals and fertilizers, equipment management, irrigation and water management and much more.